2021
DOI: 10.1101/2021.01.03.21249184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance Among Health Care Workers in the United States

Abstract: BackgroundAcceptance of the COVID-19 vaccine will play a major role in combating the pandemic. Healthcare workers (HCWs) are amongst the first group to receive vaccination, so it is important to consider their attitudes about COVID-19 vaccination to better address barriers to widespread vaccination acceptance.MethodsWe conducted a cross sectional study to assess the attitude of HCWs toward COVID-19 vaccination. Data was collected between October 7th and November 9th, 2020. We received 4080 responses out of whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
74
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 19 publications
(20 reference statements)
12
74
1
Order By: Relevance
“…16 This trend has been observed in Kuwait, 17 the general population in the United States, 18 and their health workers. 19 It is not yet clear as to why this gender difference has been continually reported in previous studies as well. 20 Men have been reported to generally take more risks in life than women.…”
Section: Discussionmentioning
confidence: 93%
“…16 This trend has been observed in Kuwait, 17 the general population in the United States, 18 and their health workers. 19 It is not yet clear as to why this gender difference has been continually reported in previous studies as well. 20 Men have been reported to generally take more risks in life than women.…”
Section: Discussionmentioning
confidence: 93%
“…While most of the KSA HCWs in our study would accept a COVID-19 vaccine, this level of acceptance (64.9%) may not be sufficient to reach herd immunity threshold, which is estimated to be between 55% and 82% ( Sanche et al, 2020 ). Additionally, COVID-19 vaccine acceptance rates among HCWs in other countries are significantly higher, such as Canada (70.4%), France (75.4%), Belgium (76.0%), China (76.4%), United States (92.0%), and Indonesia (95.5%) ( Fu et al, 2020 ; Harapan et al, 2020 ; Shekhar et al, 2021 ; Verger et al, 2021 ). However, it is important to acknowledge that reported acceptance may not always translate into actual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty and qualms HCWs went through for more than a year was bound to inculcate doubts. Only 36% of the HCWs were sure to get the vaccine as soon as it was available, as shown by a survey in November 2020, with safety, efficacy and speed of development, "too good to be true" being major concerns [48] Other studies done to explore the readiness of HCWs to get vaccinated showed similar results, with senior HCWs more likely to take the vaccine immediately [49].…”
Section: Acceptability Of Vaccines and Predictorsmentioning
confidence: 99%